Integrated use of magnetic nanostructured calcium silicate hydrate and magnetic manganese dioxide adsorbents for remediation of an acidic mine water. (October 2018) - Briso, Alejandro; Quintana, Geraldine; Ide, Viviana; Basualto, Carlos; Molina, Lorena; Montes, Gonzalo; Valenzuela, Fernando
Highlights: Acidic mine waters are decontaminated using two magnetic adsorbents. Adsorbents with strong magnetic properties allow removing pollutants from water. Magnetic nanostructured calcium silicates produces insoluble salts and hydroxides. Magnetic MnO2 removes ions via electrostatic and ion-exchange mechanisms. The decontamination treatment meets Chilean environmental regulations. Abstract: The integrated use of two solid adsorbents with magnetic properties was studied with the aim of decontaminating an acid mine water. The adsorbents were magnetic nanostructured calcium silicate hydrate (mag-NanoCSH) and magnetic manganese dioxide (mag-MnO2 ), both of which consist of a crystalline Fe3 O4 nucleus surrounded by external amorphous layers of calcium silicate and manganese oxide, respectively. They were synthesised using simple, quick, and reproducible methods. Both adsorbents were characterised chemically, physically, and magnetically via different analytical techniques. The particle size of the adsorbents varied between 60 and 200 nm, which led to a tendency to agglomerate, and the surface area varied between 30 and 70 m 2 /g. The magnetic saturation of the absorbents was found to be around 57–59 emu/g, which is sufficient to ensure complete separation of these two compounds from an aqueous raffinate using a common magnet. The nanostructure and microstructure of both adsorbents had many available adsorption sites, and their chemical structure permitted efficient and simultaneous removal of cationic and anionic species present in aqueous solutions, following different adsorption mechanisms. The influence of the main variables on the adsorption of the ionic species was studied. Samples of an acid mine water were treated using both magnetic composites consecutively. In the first step, mag-NanoCSH was able to dramatically reduce the contents of many of the ions in the treated water. Then, mag-MnO2 was added to the re-acidified raffinate produced in the first step, and the resulting final aqueous solution was found to comply with the Chilean environmental regulations.